Program Home Visit: Dampak Pengembangan Kecerdasan Majemuk Siswa Dan Pengembangan Lembaga Di Yayasan Pendidikan Islam Ulul Albab Jember - Nuruddin, Nuruddin; Bani, Bani (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2020)
This study aims to describe the implementation of the Home Visit program and its impact on the development of multiple intelligences in students as well as the institutional development at the Ulul Albab Islamic Education Foundation in Jember. This research employs a qualitative approach with a field study design. Data were collected through observations, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that the Home Visit program is systematically implemented, both through direct home visits and virtual meetings. The program positively contributes to the development of students' multiple intelligences, where teachers are able to adapt learning strategies based on each child's potential and needs. In addition, the Home Visit program strengthens the relationship between the school and parents, increases community participation, and contributes to improving the quality of the educational institution. This study recommends the continuous implementation of the Home Visit program, integrated with teacher capacity building and regular evaluations to ensure optimal outcomes.